(untitled) (The Planet, 2024)
Introduction: The use of Epidural Steroid Injections (ESIs) in treating radicular back pain due to nerve root irritation has emerged as a significant therapeutic intervention. This study examines the effectiveness of ESI in managing Lumbar Canal Stenosis (LCS) and associated radicular symptoms. Objective: To analyze the role of ESI in LCS and assess radiating pain relief and associated functional outcomes. Methods & Materials: A descriptive, prospective study was conducted between January 2020 and November 2021 at Monno Medical College Hospital. Fifty-six patients with varying presentations of low back pain were treated with epidural steroid injections. Patient outcomes were monitored through regular follow-ups, with assessment of pain relief, functional improvement, and complications. Results: Of the 56 enrolled patients (mean age 45-50 years), 54 completed follow-up. The patient distribution included 19 cases of non-radiating pain, 21 cases of single lower limb radiation, and 14 cases of bilateral lower limb radiation. Good outcomes were achieved in 32 patients (59.25%), while 19 patients (35.18%) showed satisfactory results requiring a second ESI. Only three patients (5.55%) required surgical intervention. Pain relief was typically achieved within 7-15 days post-procedure, with an average follow-up period of 1-1.5 months. Conclusion: ESI demonstrates high effectiveness in treating both radicular and non-radicular pain associated with LCS. The study supports the use of ESI as an effective non-surgical intervention, particularly when administered during the acute phase of symptoms. The transforaminal approach appears to offer superior targeting of pathology compared to the interlaminar approach, potentially yielding better outcomes. These findings suggest that ESI should be considered earlier in the treatment algorithm for appropriate candidates with LCS.